PENGELOLAAN AGROEKOSISTEM TANAMAN KOPI DI DESA WOLOGAI TENGAH - KECAMATAN DETUSOKO KABUPATEN ENDE - Murdaningsih; Josina Irene Brigita Hutubessy (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2021)
Coffee is cultivated by farmers in Wologai Village in the middle of Detusoko District, Ende Regency. Coffee plants are getting old and cannot be distributed. Agro-climate conditions are suitable for coffee plants, but coffee production is still very low. This activity aims to provide assistance to coffee farmers, with the hope that there will be an increase in the knowledge and skills of coffee farmers for the types of coffee plants, coffee plantations and coffee plantation management techniques. The target of activities in the farmer group consisting of 29 people, the activities carried out during 6 meetings, with counseling and training methods. The results of the evaluation of this service activity can increase the knowledge and skills of farmers in the aspect of agroecosystems or the environment for growing coffee plants by an average of 41.38% and farmers' knowledge regarding aspects of coffee plants increased by an average of 25.86%. ---  Kopi banyak diusahakan petani di Desa Wologai tengah Kecamatan Detusoko Kabupaten Ende. Tanaman kopi sudah berumur tua dan dibudidayakan menyebar atau tidak pada satu lahan. Kondisi Agroklimat sudah sesuai untuk tanaman kopi, namun produksi kopi masih sangat rendah. Kegiatan ini bertujuan untuk melakukan pendampingan terhadap petani kopi, dengan harapan terjadi peningkatan pengetahuan dan ketrampilan petani kopi terhadap terhadap Jenis tanaman kopi, agroekosistem tanaman kopi dan teknik pengelolaan kebun kopi. Sasaran kegiatan pada kelompok tani yang beranggotakan 29 orang, kegiatan dilakukan selama 6 kali pertemuan, dengan metode penyuluhan dan pelatihan. Hasil dari evaluasi kegiatan pengabdian ini dapat meningkatan pengetahuan dan ketrampilan petani dalam aspek Agroekosistem atau lingkungan tumbuh tanaman kopi rata-rata sebesar 41,38% dan pengetahuan petani terkait aspek tanaman kopi meningkat rata-rata sebesar 25,86%.